Density and distribution of holothuria leucospilota along the coast of dedap island, pulau abang waters - Wiranto, Ijal; Efendi, Yarsi; Agustina, Fenny (JPBIO (Jurnal Pendidikan Biologi), 2025)
The black rubber sea cucumber (Holothuria leucospilota) is prevalent along the coast of Dedap Island in Batam, unlike other sea cucumber species that face significant fishing pressure. This study examines the population and distribution of Holothuria leucospilota near Dedap Island in Abang Island, Batam. Surveys were conducted at three sites, where we carefully counted and mapped the sea cucumbers. A total of 236 individuals were recorded, with the highest density in Transect 1 (0.97/m²) and the lowest in Transect 2 (0.66/m²). Our results indicate notable variability in sea cucumber density across the surveyed areas, with some locations showing high abundance and others fewer individuals. The distribution pattern, assessed using the Morisita Index, suggested a clustering tendency, especially in Transect 1. We also examined substrate types to better understand these distribution trends. Additionally, water quality assessments showed that conditions across the transects were favourable for sea cucumber survival, with suitable levels of salinity, pH, and dissolved oxygen. These findings are vital for the management and conservation of sea cucumbers in the area.